Contemplation as an alternative to curiosity: St Bonaventure on Ecclesiastes 1:3–11. Issue 1 (9th January 2015) - Atkinson, Tyler
Abstract This article seeks to offer a christological interpretation of the opening poem in Ecclesiastes (1:3–11) through engagement with St Bonaventure's exegesis of the passage. It begins with a brief survey of contemporary treatments of the passage, which are characterised by an emphasis on cosmic monotony as an illustration of the futility of human labour. Then, it examines the Seraphic Doctor's version of the contemptus mundi interpretation of the book, relating it to his metaphysics of emanation, exemplarity and consummation. It will be suggested that Bonaventure's version of contemptus mundi informs an alternative interpretation to the critical status quo. In his exegesis of the opening poem, Bonaventure begins by describing three kinds of existence: existence in the eternal and unchanging Word, material existence in the cosmos, and abstract existence in the mind. While Bonaventure does not consider existence in the Word in relation to Ecclesiastes 1:3–11, because such existence is not subject to the vanity of mutability, the conclusion of the article will propose that such existence is in view in the text. When Bonaventure considers material existence, his metaphysics will not allow him to read the cosmological motion in Ecclesiastes 1:5–7 as monotonous, but rather as creaturely movement which invites contemplation. When he considers abstract existence, he contrasts the movement of heavenly and elemental creatures with the dissatisfaction of human perception, constrained by curiosity, the vice which characterises the protagonist's pursuits in Ecclesiastes 1:12–2:26. Thus, it will be suggested from Bonaventure's exegesis that the problem in Ecclesiastes 1:3–11 is not an oppressively monotonous universe which shows humans how pointless their own movement is, but rather humanity's failing to treat the cosmos as a book which speaks of God. In the article's final section, a relationship between the contemplative reading of Ecclesiastes 1:3–11 and Bonaventure's Itinerarium will be outlined. The consideration of material existence in Ecclesiastes 1:4–7 will be related to contemplation through vestiges. Then a contrast between the perceptual rupture of Ecclesiastes 1:8–11 and contemplation through the divine image in humanity will be shown. Finally, a christological reading of Ecclesiastes 1:10a will be offered, suggesting that this verse gestures towards the incarnate Word, who reforms the divine image in humanity and thus places humanity back on course towards similitude. It will be suggested in closing that, in signalling this hope, Ecclesiastes 1:10a prepares one for the union with Christ which Song of Songs depicts.